EFEKTIVITAS SENAM ANTIHIPERTENSI DAN SENAM YOGA TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA - Khoiroh Umah (Jurnal Keperawatan Muhammadiyah, 2023)
Objective:. The purpose of this study is to compare the effectiveness of antihypertensive and yoga exercises against changes in blood pressure in the om elderly.Methods: The design of this study used Experimental Quasy. The sampling method used Random Sampling. Samples were taken as many as 14 respondents antihypertensive and yoga exercises. The independent variable was the influence of antihypertensive exercises, carried out with a mondification of Hernawan’s theory (2017) and yoga exercise out with a modification of Hendarti’s theory (2018). The dependent variable was a decrease in blood pressure, data taken used a spignomano meterResults: It can be concluded that antihypertensive and yoga exercises are both more effective against changes in blood pressure in the elderly. The Mann whiney statistical test results obtained a sign value of two tailed p = 0.169 (p sign <0.05) so that H1 was rejected, meaning there was no difference in the decrease in blood pressure level between the antihypertensive and yoga exercises.Conclusion:This research is expected to make antihypertensive and yoga exercises as an intervention in changing blood pressure in the elderly.